Host country control over the multinational company - بختيار صابر بايز; ازاد شكور صالح (QALAAI ZANIST JOURNAL, 2019)
The multinational company is an important economic phenomenon in the field of international relations, where it is represented today as one of the influential forces in creating events and economical, social and political transformation in the contemporary world, especially in international investment relations, which is considered as one of the most important forms of foreign direct investment. Due to its role as the main channel which flows through it foreign capitals, technical knowledge and technology. In spite of the importance of these companies and their great role in the economic development of the host countries and their impact on industrial and technological progress in them, the follower of the march of these companies find that they often create a threat to the economic entity of host countries, especially the developing ones. Hence, the host country of the multinational company is entitled to be concerned about the existence of this type of companies over its territory and in its legal, commercial, economic and even political life. The host countries on one hand, want to benefit from the foreign capital brought by these companies and from the technology and development they carry, but on the other hand, it fears its control over its economy and its independence. Therefore, the encouragement of the host countries to introduce multinational companies does not mean that these companies can work as they like without limits, but with the aim of reaching limited results that can not be allowed to be overruled. Therefore the State shall observe them to ensure that they do not control their national wealth or practice unequal or undesirable competition with their national companies, national manpower or expertise. However, the host countries of the multinational company do not have to execute all kinds of observation, but it can choose what fits with their own circumstance and with the proportion that it does not impede the flow and attraction of these companies and foreign investment in general to its territory. So the purpose of monitoring multinational companies does not stop at the extent that these companies apply the provisions of the law in the host country and not to violate them, but also extended to rationalization and guidance, so that the company can perform its mission under the national plan as an effective unit in achieving economic development.